Impact of breakfast skipping toward children health: a review - Nuru, Hasanuddin; Mamang, Fardiana (International Journal Of Community Medicine And Public Health, 2017)
Breakfast skip is an activity that ignores the meal in the morning before start works, most previous studies assumed that it’s affect children health outcome. This study aim to inform the readers that how breakfast skip influence adolescent health status particularly weigh gain. This data was collected from published papers between January 2008 to 2014 used Google scholar databases. The articles were limited to English language only which focus on breakfast skip, obesity and children as keywords. Breakfast skipping has great influence to the children body particularly body mass index (BMI). Those who omit breakfast will less satiety, increase appetite and having large portion at subsequent meals, consequently total energy density higher than breakfast eaters. Breakfast skipping will lead children to the adverse health outcome especially weigh gain. Conversely, breakfast consumption is a way to ensure that they meet their daily nutrient and energy intakes.